Writer first, mother second: the politics and ethics of motherhood memoirs - Robertson, Rachel (Australasian Association of Writing Programs, 2012)
In 2009 when Julie Myerson published her creative non-fiction book The Lost Child., Minette Marrin wrote in the Times: 'Her son was betrayed because she's a writer first and a mother second.’ This was clearly meant as a damning indictment of Myerson, as was much of the press coverage of the book's representation of Myerson's teenage son and his drug habit. I compare this response to the positive reviews received by George and Sam by Charlotte Moore. Like Myerson, Rachel Cusk received a negative press when she published her 2001 motherhood memoir, A Life’s Work, with reviewers accusing her of irresponsibility, selfishness, and lack of love for her children. The public discourse used about these motherhood memoirs raises significant political and ethical issues around mothers writing autobiographically about their children. As the mother of a child with a disability who is also a memoirist, I explore how mothers writing about their children must navigate challenges to do with the construction of motherhood, the public/private split, and the archetypal splitting of mothers into good and bad. At the same time that writers such as Cusk and Myerson are condemned for exploiting their children, there has been a growth in published motherhood memoirs, including those about children with disabilities, and the so-called 'mommy blogs'. Many of these receive positive reviews and avoid the kind of public controversy caused by Cusk and Myerson. I suggest that the reason for the negative responses to Myerson and Cusk may relate more to the seriousness with which they discuss loss and motherhood, rather than the ethical issues of writing about their children. It is this seriousness and the ability to give voice to otherwise unarticulated aspects of motherhood that is of value in the work of Cusk, Moore and Myerson.